Halal cosmetics' willingness to pay for the muslim millenial generation: Lessons from Bogor Regency, Indonesia - Ramdhani, Arlita; Nursyamsiyah, Tita; Irfany, Mohammad Iqbal; Haq, Daffa Aqomal (Annals of Management and Organization Research, 2025)
Purpose: This study investigates the willingness to pay (WTP) of the Muslim millennial generation in Bogor Regency, Indonesia, for halal-certified cosmetics and analyzes the factors influencing this decision. Research Methodology: Using primary data from 100 millennial respondents collected through questionnaires, this study applied the Contingent Valuation Method (CVM) to determine WTP values. Structural equation model-partial least squares (SEM-PLS) was employed to analyze the relationship between WTP and influencing factors, including the perception of halal labels, brand image, attitude, and customer perceived value. Results: The findings indicated that millennials’ average WTP for halal-certified cosmetics was IDR 25,700. The perception of halal labels and customer-perceived value positively impact WTP, whereas brand image and attitude are not significant determinants. Conclusions: Based on these results, it can be concluded that the WTP value of the millennial generation in Bogor Regency for halal cosmetics is 25,700 per product. Limitations: This study focuses on a single region within Bogor, which limits its generalizability. Further studies should explore other regions and demographics in order to obtain broader insights. Contribution:  This study contributes to the understanding of consumer behavior regarding halal products, highlighting the importance of halal certification and perceived value. The findings could support manufacturers in improving marketing strategies and encourage policymakers to facilitate accessibility to halal certification and enhance the demand for halal products.